PENGARUH AMBIGUITAS PERAN, KONFLIK PERAN, DAN KESESUAIAN PENEMPATAN KERJA TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA KARYAWAN UNIVERSITAS MUHAMMADIYAH JEMBER) - Pratiwi, Yuli Eka; Satoto, Eko Budi; Puspitadewi S, Ira (Komunitas Manajemen Kompetitif, 2024)
This research aims to examine and analyze the influence of role ambiguity, role conflict, and work placement balance on employee performance at the Muhammadiyah University of Jember. The method used in this research is quantitative. The objects of the research were employees at the Muhammadiyah University of Jember with a population of 133 employees. The sampling technique used was probability sampling so that the sample taken in this research was 71 employees. Data collection was carried out by distributing questionnaires and measured using SPSS24. The research results show that role ambiguity, role conflict, and job placement balance have a significant effect on employee performance. The results of multiple linear regression of role ambiguity and conflict show a significant negative influence on employee performance. Meanwhile, the results of job placement suitability show a positive and significant influence on employee performance. Keywords: Employee performance, role ambiguity, role conflict, suitability of work placement.